Analysis of the Fin Incline Angle on Aerodynamic Stability of 60 mm Caliber Komando Asap Mortgarena Using Computational Fluid Dynamics Simulation Method - Lazuardi , Lazuardi; Maryono, Maryono; Ali, Muhammad; Hadi Susilo, Sugeng (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
This study aims to analyze and simulate the aerodynamic performance of the design of a training weapon grenade using the Computational Fluid Dynamics (CFD) method. CFD simulation allows the analysis of airflow around the grenade to identify the distribution of pressure, drag, and aerodynamic coefficients that play an important role in the efficiency of the grenade flight. The grenade design was tested under various conditions of speed and fin angle to understand their effects on stability and flight efficiency. The results of the simulation show that the variation of the mortar grenade with the fin position parallel to the launch angle has a fluid flow velocity of 84.1 m / s, the mortar grenade with the fin position tilted 2.5 has a fluid flow velocity of 82.7 m / s, and the mortar grenade with the fin position tilted 5 has a fluid flow velocity of 85.8 m / s from the data obtained, the inclination of the fin angle significantly affects the aerodynamic performance of the mortar grenade. This study provides insight that shifting the fin angle on the grenade can increase stability and minimize air resistance during flight.